2019
DOI: 10.3389/fmicb.2019.01106
|View full text |Cite
|
Sign up to set email alerts
|

Use of Rhizobacteria and Mycorrhizae Consortium in the Open Field as a Strategy for Improving Crop Nutrition, Productivity and Soil Fertility

Abstract: Plant growth promoting rhizobacteria (PGPR) and arbuscular mycorrhizal fungi (AMF) are known for their beneficial effects. In recent years, more attention has been paid to their use as biofertilizers to reduce the use of chemical fertilizers causing significant damage to the environment. To have high plant yields, biofertilizers may not be able to sustain plant demands and could be used in combination with chemical fertilizers. However, the application of biofertilizers in the field such as rhizobacteria and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(113 citation statements)
references
References 56 publications
6
106
0
1
Order By: Relevance
“…Microorganisms such as arbuscular mychorrhizal fungi (AMF), plant growth-promoting rhizobacteria (PGPR) or fungi play a crucial role in stimulating the growth and development of plants via a myriad of direct or indirect mechanisms such as enhanced nutrient acquisition, phytohormones production, induction of systemic resistance in plants, or competing with harmful soil microorganisms. The use of microorganisms in agriculture as biofertilizers represents an eco-friendly alternative to the chemical products that are excessively used in order to obtain high yields, which is also a new approach to the practice of organic farming [5][6][7]. According to FiBL reports, farmers are more and more oriented to organic agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms such as arbuscular mychorrhizal fungi (AMF), plant growth-promoting rhizobacteria (PGPR) or fungi play a crucial role in stimulating the growth and development of plants via a myriad of direct or indirect mechanisms such as enhanced nutrient acquisition, phytohormones production, induction of systemic resistance in plants, or competing with harmful soil microorganisms. The use of microorganisms in agriculture as biofertilizers represents an eco-friendly alternative to the chemical products that are excessively used in order to obtain high yields, which is also a new approach to the practice of organic farming [5][6][7]. According to FiBL reports, farmers are more and more oriented to organic agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…PGPR also provides nutrients to the soil by fixing nitrogen from the atmosphere and solubilizing phosphorus in the soil [26,45]. Plants with increased absorption of nitrogen and phosphorus can promote photosynthesis and protein biosynthesis, thus increasing the size and yield of the fruit [46][47][48][49]. In cultivated orchard experiments, the size and yield of jujube fruits from trees inoculated with L. antibioticus HS124 were significantly increased (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Well development in root system of trees are the most essential attribute for enhancing minerals and nutrient uptake [25,27,28,49]. Auxin produced by L. antibioticus HS124 inoculation might promote root development and stimulate the formation of absorbent root hairs and lateral roots [24,25,27,28,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in agreement with those obtained by Najafi et al, (2012) who found positive effects of microorganism symbiosis on barley root growth and water and nutrition absorption. In addition, Raklami et al, (2019) pointed out a positive impact of biofertilizers and interest of adoption of innovative practices improving crops productivity and soil fertility. Berhanu et al, (2013) reported that there was a positive effect of using Mycorrhizae and Azotobacter on wheat crop yield.…”
Section: Effect Of Bio-fertilizers On Yield Parametersmentioning
confidence: 99%